Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol